KEADILAN RESTORATIF BAGI KORBAN PENYALAHGUNAAN NARKOTIKA: OPTIMALISASI KAMPUNG TANGGUH KABUPATEN PATI DALAM PERSPEKTIF INTEGRATED CRIMINAL JUSTICE SYSTEM - Lailatul Nur hasanah (Yayasan Merassa Indonesia Publikasi, 2026)
The law enforcement of narcotics crimes in Indonesia is currently faced with a paradigmatic misalignment between punitive-retributive and restorative recovery approaches. This study aims to analyze the effectiveness and accountability of law enforcement officials in differentiating sanction articles between dealers and users, identify the determinant factors inhibiting the implementation of rehabilitation policies at the rural level, and formulate strategies to optimize the